Intuitive eating reduced dietary restraint in university students during the covid-19 pandemic: a cohort study (Revista Contexto & Saúde, 2026)
Objective. To assess the practice of restrictive dieting among university students, its associated factors, and the role of intuitive eating during the first and second years of the COVID-19 pandemic in Brazil. Method. This is a longitudinal study, with the first data collection carried out in the first bimester of the pandemic and the beginning of social distancing measures in Brazil (May 2020), and the second data collection carried out in the second year of the pandemic (March 2021). The study population consisted of 293 undergraduate students from a federal university in southeastern Brazil. The survey was conducted through an online questionnaire (with self-reported information) and participants were invited via institutional email and social media promotion. Results. It was observed that being overweight (OR=2.415; CI=1.326–4.397; p=0.004), following fitness/health-related social media profiles (OR=1.915; CI=1.093–3.355; p=0.023), and being at risk for eating disorders (OR=2.531; CI=1.352–4.739; p=0.004) were associated with engaging in restrictive dieting among university students at the beginning of the COVID-19 pandemic. Additionally, engaging in physical activity (OR=2.852; CI=1.473–5.521; p=0.002) and concern about weight gain (OR=2.484; CI=1.235–4.996; p=0.011) were associated with the same outcome in the second year of the pandemic. Conversely, intuitive eating was associated with a lower likelihood of practicing a restrictive dieting (OR=0.601; CI=0.372–0.970; p=0.037). Furthermore, a decrease in dieting practices was observed over the follow-up (p
Keywords: Feeding Behavior; Intuitive Eating; Diets; Longitudinal Studies; COVID-19